PROBLEMS OF FORMING STUDENTS’ COMPLETE KNOWLEDGE ABOUT LIVING NATURE WHEN STUDYING NATURAL SCIENCE DISCIPLINES - Мельничук, О.Д.; Рожі, І.Г. (Modern engineering and innovative technologies, 2023)
The article defines the task of forming knowledge about nature during the study of natural sciences, which are common to biology, geography, physics, chemistry and other branches of natural science. The general content lines of the educational field from